Rapid-Antigen Test Negative Malaria in a Traveler Returning From Thailand, Molecularly Diagnosed as Plasmodium knowlesi. (21st March 2016) - Mackroth, Maria S.; Tappe, Dennis; Tannich, Egbert; Addo, Marylyn; Rothe, Camilla
Abstract: Plasmodium knowlesi has been identified in the last decade as a fifth species causing malaria in areas of South East Asia. Due to its short erythrocytic cycle, rapid development of high parasitemia and severe manifestations are frequently observed. Therefore, prompt diagnosis of infection is essential to prevent complications, but the low sensitivity of rapid diagnostic tests for P knowlesi pose a diagnostic challenge in acute settings. In this study, we report the case of a German traveler to Thailand, who was treated for P knowlesi malaria after returning to Germany. Rapid antigen test for malaria was negative on presentation. Diagnosis of a nonfalciparum malaria was made based on microscopy, and species definition was determined using polymerase chain reaction technique.